Observation of Puerperal Condition among The Patients (The Planet, 2023)
Introduction: Puerperal condition refers to the physical and emotional state of a woman during the postpartum period, which typically lasts six weeks after giving birth. It is common for women to experience a variety of symptoms during this time, including fatigue, pain, bleeding, and hormonal changes. Aim of the study: The aim of the study was to observe the puerperal conditions among patients admitted at the Enam Medical College Hospital. Methods& Materials:This cross-sectional observational study was conducted at the Department of Obstetrics and Gynecology, Enam Medical College Hospital, Dhaka, Bangladesh. The study duration was 6 months, from January 2022 to July 2022. During this period, a total of 60 patients who had given birth in the study place were included in the study. Results: The study involved 60 participants,  and 40% of the participants had been pregnant for 35-37 weeks, and 66.66% of them had a historyof cesarean section. Lower abdominal pain was the most common complaint at 40%.Mean pulse, systolic and diastolic BP were above the normal range, and 66.67% of the participants had tenderness at the suture area. The mean weight of the neonates was 2.749 ± 0.497 kg, with 36.67% having low birth weight. Conclusion: Most participants were young, many had a cesarean section and comorbidities. Post-delivery variables were above the normal range and many participants had tenderness as a post-delivery complication. The study highlights the need for appropriate care during the postpartum period.
Keywords: Puerperal; Pregnancy; Complication; Symptoms